2020
DOI: 10.1115/1.4046127
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Anisotropic Material Properties of Soft Tissue by MRI of Ultrasound-Induced Shear Waves

Abstract: This paper describes a new method for estimating anisotropic mechanical properties of fibrous soft tissue by imaging shear waves induced by focused ultrasound (FUS) and analyzing their direction-dependent speeds. Fibrous materials with a single, dominant fiber direction may exhibit anisotropy in both shear and tensile moduli, reflecting differences in the response of the material when loads are applied in different directions. The speeds of shear waves in such materials depend on the propagation and polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Three ITI material parameters have been measured in vivo by magnetic resonance elastography (MRE) [48], and in ex vivo animal tissue [49], [50]. Looking at the three muscles in the calf using MRE in vivo, Guo et al [48] found lower χ µ values (soleus 0.50, gastrocnemius 0.80, tibialis anterior 0.27) compared to χ µ = 2.11 herein for vastus lateralis, and also χ E values lower than herein (soleus 1.47, gastrocnemius 2.26, tibialis 2.00, compared to χ E = 4.67 for vastus lateralis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three ITI material parameters have been measured in vivo by magnetic resonance elastography (MRE) [48], and in ex vivo animal tissue [49], [50]. Looking at the three muscles in the calf using MRE in vivo, Guo et al [48] found lower χ µ values (soleus 0.50, gastrocnemius 0.80, tibialis anterior 0.27) compared to χ µ = 2.11 herein for vastus lateralis, and also χ E values lower than herein (soleus 1.47, gastrocnemius 2.26, tibialis 2.00, compared to χ E = 4.67 for vastus lateralis).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies to date have measured the directional dependence of shear wave propagation in muscle, reporting a wide range of speeds along and across the fiber axis [16], [24], [36]- [50]. These reports used an experimental setup similar to that shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As our method delineated, when the mechanical properties of axonal fibers and ECM are coupled with imaging data, it can offer new tools to boost the MRE capabilities to depict the anisotropic stiffness of brain 107 , and identify or evaluate brain disorders such as Alzheimer's 14,15,76 , Parkinson's 16 , and multiple sclerosis [108][109][110] . With the aim of achieving this, extensive recent efforts have focused on connecting MRE and DTI for predicting anisotropic mechanical properties of the brain tissue of the human or other species [111][112][113][114][115] . It has been shown that there are strong correlations between the mechanical properties assessed by MRE in the CC and CR and microstructural properties derived from DTI 107 .…”
Section: Discussionmentioning
confidence: 99%
“…The displacement field acquired from MRE is inverted to estimate mechanical properties, such as stiffness and damping [36][37][38][39] . In recent years, there has been a shift towards incorporating anisotropy considerations in MRE, which previously predominantly used inversion models assuming mechanical isotropy [40][41][42] . Despite the promising advantages of MRE, there are ongoing efforts to improve the accuracy of entire process, encompassing imaging, wave generation, actuation frequency, acquisition strategy, physiological vibration analysis, inversion algorithms, and processing pipelines.…”
Section: Introductionmentioning
confidence: 99%